Blasting Geometry Engineering for the Use of Explosives Based on Linear Functions in Andesite Mining - Sartika, (ReTII, 2024)
Mining of andesite at PT. Pro Intertech Indonesia is carried out through drilling and blasting activities using explosives in the form of Ammonium Nitrate and Fuel Oil (ANFO). In calculating the use of explosives based on blast geometry, several methods are used, including the theory of The Modern Technique of Rock Blasting, the ICI-Explosive theory, and linear functions based on correlation graphs. The actual blast geometry in the field has short burden, spacing, and stemming, as well as a high bench height and long charge column length, resulting in the use of 46.98 kg of explosives with fragmentation results of approximately 16 cm. Based on the designed geometry, the use of explosives would be reduced by using the ICI-Explosive theory. However, the geometry design recommended by the author is to use The Modern Technique of Rock Blasting theory, as a smaller powder factor can minimize blasting effects such as fly rock and vibration, which impact the environment. The resulting geometry design includes a burden and stemming of 2.68 m, spacing of 3.34 m, subdrilling of 0.91 m, bench height of 10.66 m, and charge column length of 9.28 m. This geometry design uses 46.19 kg of explosives per blast hole and produces a blast production volume of 243.34 tons, with fragmentation results of 20.17 cm.